Polskie biblioteki ludowe na pograniczu zachodnim: w rejonie Babimojsko-Międzyrzecko-Skwierzyńskim w latach 1880-1939 - Chmielewski, Grzegorz (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
This work documents the history and activities of Polish folk libraries in the Babimost-Międzyrzec-Skwierzyna region between 1880 and 1939. The author focuses on the role that books and reading played in preserving the national identity of Poles in territories under German rule. The publication was created thanks to the discovery of material evidence of the existence of libraries ? specific volumes with seals and bookplates. A key figure was Waleria Misiewicz, who stored books from the Pszczew parish in the attic of her house in Szarcz, protecting them from destruction by the Germans. The author examines the activities of two key organizations: the Society of Folk Reading Rooms (TCL), which conducted extensive educational activities, and the Union of Catholic Societies of Polish Workers. The author discovered a previously unknown network of libraries of this association, operating in the Archdiocese of Gniezno-Poznań. Due to the destruction of the TCL central archive in Poznań during the war, the author based his research on painstaking research in parish archives (including those in Babimost and Pszczew) and on an analysis of preserved book collections donated to the Central Oder Book Museum in Zielona Góra. The introduction outlines the dramatic fate of Polish collections that survived Prussian indexes of forbidden books and Nazi purges, only to be frequently discarded after 1945 as a result of Stalinist crackdowns on public libraries. The publication aims to exhaustively utilize the discovered material sources and present them in the form of appendices (catalogs of preserved and lost books), thus documenting Polish cultural activity in these areas.
Keywords: księgozbiory; działacze polonijni; Towarzystwo Czytelni Ludowych; Związek Katolickich Towarzystw Robotników Polskich; Międzyrzecz (woj. lubuskie); Babimost (woj. lubuskie, pow. zielonogórski, gm. Babimost); Nowe Kramsko (woj. lubuskie, pow. babimojski, gm. Babimost); Pszczew (woj. lubuskie, pow. międzyrzecki, gm. Pszczew); Skwierzyna (woj. lubuskie, pow. międzyrzecki, gm. Skwierzyna); biblioteki polskie; biblioteki ludowe; zabór pruski; library collections; Polish diaspora activists; Prussian Partition; Polish libraries; People's Libraries Society